Khatam Al-Khawjakan In Naqshabandi Mujaddidi Ahmadi Taught By Shaykh Islam Wan Sulaiman Wan Sidek (D.1354h/1935M) - Muhammad Khairi Mahyuddin (Center for Promoting Education and Research (CPER) USA, 2024)
Volume: 7 No: 7